Metabolic imaging using hyperpolarized 13C‐pyruvate to assess sensitivity to the B‐Raf inhibitor vemurafenib in melanoma cells and xenografts. Issue 2 (13th December 2019) - Acciardo, Stefania; Mignion, Lionel; Lacomblez, Estelle; Schoonjans, Céline; Joudiou, Nicolas; Gourgue, Florian; Bouzin, Caroline; Baurain, Jean‐François; Gallez, Bernard; Jordan, Bénédicte F.
Abstract: Nearly all melanoma patients with a BRAF‐activating mutation will develop resistance after an initial clinical benefit from BRAF inhibition (BRAFi). The aim of this work is to evaluate whether metabolic imaging using hyperpolarized (HP) 13 C pyruvate can serve as a metabolic marker of early response to BRAFi in melanoma, by exploiting the metabolic effects of BRAFi. Mice bearing human melanoma xenografts were treated with the BRAFi vemurafenib or vehicle. In vivo HP 13 C magnetic resonance spectroscopy was performed at baseline and 24 hours after treatment to evaluate changes in pyruvate‐to‐lactate conversion. Oxygen partial pressure was measured via electron paramagnetic resonance oximetry. Ex vivo qRT‐PCR, immunohistochemistry and WB analysis were performed on tumour samples collected at the same time‐points selected for in vivo experiments. Similar approaches were applied to evaluate the effect of BRAFi on sensitive and resistant melanoma cells in vitro, excluding the role of tumour microenvironment. BRAF inhibition induced a significant increase in the HP pyruvate‐to‐lactate conversion in vivo, followed by a reduction of hypoxia. Conversely, the conversion was inhibited in vitro, which was consistent with BRAFi‐mediated impairment of glycolysis. The paradoxical increase of pyruvate‐to‐lactate conversion in vivo suggests that such conversion is highly influenced by the tumour microenvironment.